Development of Ability Testing Instruments Based on Sensor Technology - Putra, Surya Pradana; Hartati, Hartati; Safaruddin, Safaruddin (Department of Physical Education, Sport, Health and Recreation, 2021)
This study aims to develop a sensor technology based agility test instrument. The research method used is research and development (research and development). Development research subjects were divided into two groups. Small-scale group trials consist of 10 students and large-scale group trials consist of 21 students. The results showed that the sensor technology-based push-up test instrument had a 94% validity test and sports measurement expert level and 75% IT expert validity so that it could be used appropriately. The level of reliability in small group trials amounted to 0.994 and small groups of women amounted to 0.988 with the High category. While the large group trials amounted to 0.998 and the large group of women 0.946 with a high category so that it can be held accountable for the tools carried out in large group trials and small groups have a High reliability category. The implication of this research is the development of test instruments based on sensor technology that can be used as a valid, effective, and practical test aid.